(untitled) (Proceedings of the International Conference on Education, 2021)
: The pandemic has posed many challenges for the academic continuity of clinical training. The social responsibility of universities and the professionalism of physicians inspired residents on taking the leadership in the front line of COVID-19. Their direct involvement in patient care required the establishment of protocols to offer mentoring and support services for self-care and mental health strategies to prevent burnout. The objective of this study was to describe the design and implementation of a comprehensive strategy to transform the Multicentric Program of postgraduate medical education in northern Mexico to continue academic and clinical training activities amid the pandemic. The participants in this study include six training centers which represent 290 physicians in 17 medical specialties programs. The results of the designed strategy focus on three specific activities: 1) offering formal curricular elements through online platforms and mobile devices, 2) adaptative clinical training for the residents participating directly in SARS-Cov2 patient care, and 3) specific training on COVID-19 for all participants on patient safety protocols and use of protective equipment. All 17 programs achieved academic continuity by the use of digital platforms. The protection and safety of the educational community were privileged with the purpose of training by providing residents specific safety training on COVID-19, personal protection equipment, periodical PCR testing and by the vaccination strategy. The responsibility and responsiveness of educational institutions to address the challenges to continue the clinical training during the health crisis will significantly affect the educational results and preparedness of the next generation of health professionals. The commitment of universities should be beyond academic continuity or sharing content online, it should address as well self-care and wellbeing strategies that could provide graduates with the skills that are essential to thrive in the current pandemic.